2015
DOI: 10.1007/978-3-319-18032-8_32
|View full text |Cite
|
Sign up to set email alerts
|

A Feature Extraction Method for Multivariate Time Series Classification Using Temporal Patterns

Abstract: Abstract. Multiple variables and high dimensions are two main challenges for classification of Multivariate Time Series (MTS) data. In order to overcome these challenges, feature extraction should be performed before performing classification. However, the existing feature extraction methods lose the important correlations among the variables while reducing high dimensions of MTS. Hence, in this paper, we propose a new feature extraction method combined with different classifiers to provide a general classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…After studying the sea clutter, Yokoyama et al (2015) found that sea clutter was also chaotic. This discovery has strongly impacted the traditional signal detection theory to cross chaos theory with other disciplines, making the application of chaos theory further (Zhou and Chan 2015). The development, for example, combines chaos theory with information processing.…”
Section: Related Workmentioning
confidence: 99%
“…After studying the sea clutter, Yokoyama et al (2015) found that sea clutter was also chaotic. This discovery has strongly impacted the traditional signal detection theory to cross chaos theory with other disciplines, making the application of chaos theory further (Zhou and Chan 2015). The development, for example, combines chaos theory with information processing.…”
Section: Related Workmentioning
confidence: 99%
“…At present, the sequence in sequence classification is a time series. Every sequence associates a label, and every sequence have a fixed length in order to be available to a specified classifier [13]. Therefore, the fault diagnosis of bearings using vibration signal can be categorized to sequence classification through Naïve Bayes classifier.…”
Section: Sequence Classificationmentioning
confidence: 99%
“…These large-scale data encode important information about complex relations among individual time series. Recent works on multivariate time-series (MTS) pattern discovery focus mainly on extracting temporal association patterns and features [1][2][3]. Many of these MTS are spatio-temporal by nature in which they are collected together with location information such as latitude and longitude.…”
Section: Introductionmentioning
confidence: 99%